Penerapan PjBL Terintegrasi STEAM melalui Proyek Mini Riset Data Kontekstual untuk Meningkatkan Literasi Numerasi Siswa Kelas IV SD - Kiswoyo, Sinta; Lilik Bintartik; Hinggar Relung Puspita; Devi Restu Putpitasari; Alviena Tazky Amalia; Amida Suaidah; Aldi Surya Kinasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the STEAM-integrated Project Based Learning (PjBL) model through a contextual mini research project and to analyze its effect on improving the numeracy literacy skills of fourth-grade elementary school students. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in one cycle consisting of three meetings. The participants were 27 fourth-grade students. Data were collected through numeracy literacy tests, learning implementation observation sheets, student activity observations, project assessments, interviews, and documentation. Quantitative and qualitative data analyses were conducted by calculating mean scores, learning mastery percentages, and normalized gain (N-Gain) scores, supported by descriptive analysis. The findings revealed that students’ average numeracy literacy score increased from 32.1% in the pretest to 74.1% in the posttest, representing an improvement of 42.0%. Learning mastery also increased from 25.9% to 77.8%, exceeding the predetermined success criterion of 75%. The calculated N-Gain score was 0.62, which falls into the moderate category. In addition, the implementation of learning activities improved from 66.7% in the first meeting to 88.9% in the third meeting. The contextual mini research project achieved an average score of 80.2, categorized as good. These findings indicate that the implementation of STEAM-integrated Project Based Learning through a contextual mini research project is effective in improving elementary school students’ numeracy literacy skills